1999
DOI: 10.1152/ajpheart.1999.276.2.h530
|View full text |Cite
|
Sign up to set email alerts
|

Human endothelial cells produce orosomucoid, an important component of the capillary barrier

Abstract: The serum protein orosomucoid (α1-acid glycoprotein) is needed to maintain the high capillary permselectivity required for normal homeostasis. It is not known how the protein executes its action, but it seems to contribute to the charge barrier. Moreover, recent studies suggest that the endothelial glycocalyx is essential for the charge barrier. The main site of orosomucoid synthesis is the liver, but we wanted to explore the possibility that orosomucoid was synthesized in endothelial cells. Primary cultures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 25 publications
2
73
0
Order By: Relevance
“…Orosomucoid, a plasma glycoprotein, which is synthesized in the liver and may be also secreted by endothelial cells, 38 increases several folds during infection or trauma. 29,35 Orosomucoid is also bound to the surface of cultured bovine pulmonary microvascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orosomucoid, a plasma glycoprotein, which is synthesized in the liver and may be also secreted by endothelial cells, 38 increases several folds during infection or trauma. 29,35 Orosomucoid is also bound to the surface of cultured bovine pulmonary microvascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…36 It has been found that orosomucoid modulates the transport of charged solutes across the wall of peripheral and cerebral microvessels in vivo by decreasing the transport of negatively charged molecules but increasing that of positively charged ones, 13,23,46 suggesting that orosomucoid plays an essential role in maintaining the permeability property of endothelium by adding negative charge to the SGL. 13,23,38 The second objective of the present study is thus to investigate whether orosomucoid modulates the bEnd3 monolayer permeability in a similar way as it does for the intact endothelium of the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…AGP is considered as a minor acute phase protein in cattle since its concentration increases only two-to four-fold during inflammation [30]. As the other acute phase proteins, AGP is produced mainly by hepatic cells, but local expression has been reported in human breast epithelial cells [11], stimulated alveolar macrophages [7] and human endothelial cells [29]. The detection of two of the major bovine APP, haptoglobin and serum amyloid A (SAA) in milk during mastitis [5] may suggest a role for APP also in the immunomodulation of the local inflammatory reaction in the udder.…”
Section: F Ceciliani Et Almentioning
confidence: 99%
“…Although extrahepatic production of this glycoprotein has also been described, its biological significance is still obscure (Gahmberg and Andersson, 1978;Sörensson et al, 1999;Fournier et al, 1999Fournier et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%